Determination of Electrode Oxygen Transport Kinetics Using Electrochemical Impedance Spectroscopy Combined with Three-Dimensional Microstructure Measurement: Application to Nd2NiO4+δ - Yakal Kremki, Kyle (2014)
Oxygen reduction kinetic parameters – oxygen ion diffusion Dδ, molar surface exchange rate ℜO and surface exchange coefficient k – were determined for porous Nd2NiO4+δ solid oxide fuel cell cathodes as a function of temperature and oxygen partial pressure by analyzing electrochemical impedance spectroscopy data using the Adler-Lane-Steele model. Electrode microstructural data used in the model calculations were obtained by three-dimensional focused ion beam-scanning electron microscope tomography. Cathodes were fabricated using Nd2NiO4+δ powder derived from a sol-gel method and were tested as symmetrical cells with LSGM electrolytes. The oxygen surface exchange rate exhibited a power-law dependency with oxygen partial pressure, whereas the oxygen diffusivity values obtained varied only slightly. The present analysis suggests that the O-interstitial diffusion has a bulk transport path, whereas the surface exchange process involves dissociative adsorption on surface sites followed by O-incorporation. For Nd2NiO4+δ at 700°C and 0.2 atm oxygen pressure, Dδ = 5.6·10−8 cm2s−1, ℜO = 2.5·10−8 mol·cm−2 s−1. The present Dδ and ℜO values and their activation energies are slightly different to those previously reported for Nd2NiO4+δ using other measurement methodologies, and lower than typical state-of-the-art Co-rich perovskites. However, the average kδ = 1.0 10−5 cm·s−1 at 700°C is comparable to those of fast oxygen exchange rate perovskites.